Are African governments serious about agriculture? - Benin, Samuel (International Food Policy Research Institute, 2013)
The objective of this brief is to analyze available data on public agriculture expenditure in Africa—with a particular focus on Ghana—to assess the commitment of African governments to the agriculture sector, which they themselves have formally identified as the lead sector for achieving growth, raising incomes, reducing poverty, and increasing food and nutrition security.